PROSPEK JENIS TANAMAN PISANG UNTUK DILAKUKAN OLEH KELOMPOK USAHA TANI - Nashar Nashar (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
The Research aims to know the advisability and investment banana crop farming in increasing income of farmers in the village of Ponteh, Subdistrict of Galis, Regency of Pamekasan. The population in this researh is a banana farmer in the village of Ponteh, Subdistrict of Galis, regency of Pamekasan. For this study, researchers determined the total sample of 475 people, but the questionnaire who managed to return only 83 respondents. To test the hypothesis uses analysis factor. The Research result showed Plantain crop farming that is done in the village of Ponteh, Subdistrict of Galis, Regency of Pameksan is not worth the effort seen from the financial aspect, namely payback period of 1 year 8 months longer than the economic age is 1 year. Market aspects, technical aspects, and social aspects are in good category with score average of consecutive 4.15, 4.06, and 4.03. The number of workers absorbed in full from plantain crop farming in a year as many as 179 people. Obstacles in the plantain crop farming in the village of Ponteh, Subdistrict of Galis, regency of  Pameksan are: the technical Obstacles is the harvest plantain difficult set according to market needs. and drugs required are not available in the village. Nontechnical Obstacles is the selling price of plantain is determined by the buyer (collector) so that the farmers' bargaining position is weak, the selling price of plantain is not stable, the land area of the narrow become an obstacle in the development of crop farming of bananas, the group of farmer as a forum for farmers of plantain crop to hold interaction is not functioning optimally